Responding to burns - is our practice adequate? - Ahmed, Moiz; Zahid, Ibrahim (Journal of the Pakistan Medical Association, 2023)
Madam, Around 90% of burn related injuries are seen in low- and middle-income countries. Misfortune of such incidents lies in the fact that most of these are either preventable in the first place or can be efficiently managed before the casualty reaches the healthcare centre. According to a study1 conducted in Burns Ward of Civil Hospital Karachi, around 1,979 patients with burn-related injuries were admitted in just two-year period. Out of which, 715 patients (36.12%) expired. This mortality rate was higher in females (39.40%) and in people older than 60 (47.90%). A massive chunk of these deaths was accidental (95.80%), imposing the need to address the root cause of the issue. Another study2 showed that around 76% of students had never attended any formal training related to burns first aid management which is quite alarming. This again implies the extreme necessity to train and enable the masses to face burn related accidents. Another real dread comes with the prevalence of myths in the community that lead to the worsening burn wounds at home. According to a study3 conducted in POF hospital in Wah Cantt, a statistically significant (81.28%, p<0.05) number of people lacked the understanding of burns first-aid. A vast fraction did not take immediate action upon facing a burn wound, making awareness sessions an exigency for such epidemiology. Another similar study4 interviewed parents and showcased that around 86.8% of parents didn’t irrigate the burn wound with tap water, which is considered a standard intervention for burn injury. Instead, a significant ratio (30%, p<0.05) of parents used traditional remedies, among which toothpaste application (16.70%) tops the list. FRIP (First Response Initiative of Pakistan) is a non-governmental organization founded in 2010 aimed to educate the masses about the pre-hospital management of traumatic and non-traumatic injuries. One such aspect of its curriculum is burn management. Over more than ten years, it has instilled a standard method of burn wound care based on AHA’s (American Heart Association) guidelines among the masses and has taught ways to prevent it too. The effectiveness of such workshops is evidenced in a relevant study5 which reveals that a statistically significant difference (p<0.05) existed after similar sessions conducted as illustrated in Figure 1. These figures prove the importance of first aid workshops and the crucial role FRIP plays in solving pre-hospital burn management problems.